THE SEROLOGICAL DIFFERENTIATION OF PATHOGENIC AND NON-PATHOGENIC STRAINS OF HEMOLYTIC STREPTOCOCCI FROM PARTURIENT WOMEN - Lancefield, Rebecca C. (The Rockefeller University Press, 1935)
1. The majority of strains of hemolytic streptococci from puerperal infections of the uterus were identified serologically as members of the Group A described by Lancefield. 2. The majority of strains isolated from the birth canal of women whose puerperium was afebrile were not members of Group A. 3. The existence of two new serological groups of hemolytic streptococci, Groups F and G, is described.